Impact of Front Line Demonstrations on the Yield and Economics of Pulse Crops in Burhanpur District of Madhya Pradesh (Indian Journal of Extension Education, 2019)
The study was carried out in adopted villages of Krishi Vigyan Kendra, Burhanpur during 2013-14 to 2018-19. Total 100 front line demonstrations were conducted on pulses i.e. black gram, soybean, pigeon pea, chickpea and green gram in 40 hectare by the active participation of the farmers for adoption of improved technologies of pulse production potentials. The improved technologies included use of new variety and full package of practices i.e. seed treatment, integrated nutrient management, integrated pest management, irrigation, harvesting, storage and post-harvest management. FLD plot recorded higher yield as compared to farmer’s local practice. The mean data revealed that an average yield recorded was 15.74 q/ha under demonstrated plots as compare to farmers practice 12.50 q/ha. Additional yield over local check was 3.04 q/h with percent increased yield of 19.38 per cent. The improved technologies gave higher gross return (Rs 65870/ha), net return (Rs. 46510/ha) with higher benefit cost ratio (3.09) as compare to farmer’s practice (2.52).